"Stimulated by these agents to vigorous action": the language of suntanning and materiality of skin in Victorian culture. (2nd January 2022) - Mathieson, Charlotte
ABSTRACT: This paper explores the materiality of skin as it is figured and re-figured through sunburn and suntanning descriptions in nineteenth-century culture. In nineteenth-century literary representations, the suntanned skin of white, British subjects is depicted through a rich array of terminology attending not only to the transformation of colour but also to the surface texture of the skin. This article identifies that, amid changing ideas about the embodiment of self within the skin, suntanning representations bring to the surface a particular ambivalence around the stability of the skin that manifests through explorations of the reconfiguration of the skin surface. The article analyses the language of suntanning to explore, firstly, how the action of sunburn and tanning reveals the skin as unstable and susceptible to the invasive actions of the sun, endangering the boundary-lines of the physical and conceptual self; and, secondly, instances in which suntanned skin is conceptualised through likeness to material objects in a way that metaphorically and conceptually hardens the skin and self against the wider world.